2017
DOI: 10.1186/s12907-017-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of poorly differentiated thyroid carcinoma probably arising from a nodular goiter

Abstract: BackgroundSome poorly differentiated thyroid carcinomas (PDTC) arise from pre-existing, well-differentiated carcinomas of follicular cell origin; however, others most likely arise de novo. The case of a PDTC adjacent to a pre-existing nodular goiter is very rare.Case presentationA patient had a PDTC, a widely invasive, cellular tumor with cells that lacked the nuclear features of a papillary thyroid carcinoma. Carcinoma cells were arranged in trabecular, solid, and microfollicular histological patterns and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The rarity of this neoplasm and the heterogeneity of histologic features highlight a major diagnostic challenge. PDTC constitutes ~4% of all thyroid neoplasms and mainly affects females in their fifth age similar to our case 5 , 6 .…”
Section: Discussionsupporting
confidence: 81%
“…The rarity of this neoplasm and the heterogeneity of histologic features highlight a major diagnostic challenge. PDTC constitutes ~4% of all thyroid neoplasms and mainly affects females in their fifth age similar to our case 5 , 6 .…”
Section: Discussionsupporting
confidence: 81%
“…Primary thyroid tumors were classified according to the most recent World Health Organization criteria with the exception of tall cell variant (TCV-PTC) and poorly differentiated thyroid cancer [6]. Tumors were classified as TCV-PTC if they contained ≥ 50% tall cells.…”
Section: Tumor Histologymentioning
confidence: 99%
“…Therefore, the authors suggested that the majority of anaplastic thyroid carcinomas arise de novo rather than through clonal transformation of well-differentiated thyroid carcinomas [ 80 ]. However, the genetic alterations in cases of poorly differentiated thyroid carcinomas arising within a nodule of goiter, thus paradigmatic of de novo origin, are unspecific (i.e., NRAS mutations) [ 81 ].
Fig.
…”
Section: Molecular Mechanisms Of Progression From Well-differentiatedmentioning
confidence: 99%